BALB/c mice infected with Angiostrongylus cantonensis: A new model for demyelination in the brain. Issue 5 (23rd October 2020) - Xiong, Huihui; Zhou, Zongpu; Wu, Zhongdao; Feng, Ying; Xie, Fukang
Abstract: In this study, we present a new model for demyelination of the central nervous system (CNS). BALB/c mice were infected with Angiostrongylus cantonensis and analyzed 7, 14, and 21 days postinfection. Neurological scale evaluation, magnetic resonance imaging (MRI), histology, real‐time quantitative polymerase chain reaction, and western blotting were all performed on days 7, 14, and 21. The results showed that the neurological functions and weight of A. cantonensis ‐infected mice decreased markedly after 21 days of infection. MRI showed subdural effusion and white high signals in the corpus callosum in both T1WI and T2WI, while hematoxylin and eosin and luxol fast blue staining showed hemorrhage and demyelination in the corpus callosum. Transmission electron microscopy revealed that the ultrastructure of the myelin sheath in the corpus callosum was dispersed or disintegrated. The percentage of myelinated axons was significantly decreased, and the g ‐ratio was lower than that in the normal group. Both protein and mRNA levels of myelin basic protein decreased markedly at 21 days postinfection. Immunofluorescence revealed that the number of CC1 positive cells in the corpus callosum also decreased, which confirmed the damage of A. cantonensis to oligodendrocytes. Our experiments confirmed that A. cantonensis infection caused demyelination in the CNS of BALB/c mice after 21 days, and its clinical manifestations and pathological changes were similar to those of multiple sclerosis and other CNS demyelination models. Thus, mice infected with A. cantonensis could be used as a new model to study acute demyelination of the CNS.